Kontribusi Spiritualitas Pelayanan Prodiakon di Paroki Kristus Raja Baciro dalam Memaknai Tugasnya - Enda, Matius; Rukiyanto, Bernardus Agus (Fakultas Teologi, Universitas Sanata Dharma, 2024)
Prodiakon of Christ the King Baciro Parish is one of the forms of lay involvement in taking part in the service of the Church. The call to be a prodiakon is not only to relieve the priest's duties, but the prodiakon is expected to realise his special service specifically during the Eucharist celebration. The purpose of the study was to find out the description of the spirituality of prodiakon service in interpreting their duties. Prodiakon has a noble service in the celebration of the Eucharist, God's own means of channeling His grace through the gift of His Body and Blood for the Christian faithful. The author uses qualitative research methods. Data sources were obtained from interviews and observations. From the results of the research, the author found that the spirituality lived by prodiakon can support the task of service and can live it with joy, love, and humility.AbstrakProdiakon Paroki Kristus Raja Baciro menjadi salah satu bentuk keterlibatan kaum awam dalam ambil bagian pelayanan di Gereja. Panggilan Menjadi prodiakon tidak hanya sekedar meringankan tugas imam, tetapi prodiakon diharapkan menyadari pelayanannya yang istimewa secara khusus saat perayaan Ekaristi. Tujuan dari penelitian untuk mengetahui gambaran spiritualitas pelayanan prodiakon dalam memaknai tugasnya. Prodiakon memiliki pelayanan yang mulia dalam perayaan Ekaristi, sarana Allah sendiri dalam menyalurkan rahmat-Nya melalui anugerah Tubuh dan Darah-Nya bagi umat beriman kristiani. Penulis menggunakan metode penelitian kualitatif. Sumber data diperoleh dari wawancara dan observasi. Dari hasil penelitian, penulis menemukan bahwa spiritualitas yang dihidupi oleh prodiakon dapat mendukung tugas pelayanan dan dapat menjalaninya dengan penuh sukacita, kasih, dan kerendahan hati.